2015
DOI: 10.1093/femsyr/fov115
|View full text |Cite
|
Sign up to set email alerts
|

Nectar yeasts of theMetschnikowiaclade are highly susceptible to azole antifungals widely used in medicine and agriculture

Abstract: The widespread use of azole antifungals in medicine and agriculture and the resulting long-persistent residues could potentially affect beneficial fungi. However, there is very little information on the tolerance of non-target environmental fungi to azoles. In this study, we assessed the susceptibility of diverse plant- and insect-associated yeasts from the Metschnikowia clade, including several ecologically important species, to widely used medical and agricultural azoles (epoxiconazole, imazalil, ketoconazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
(72 reference statements)
2
26
0
Order By: Relevance
“…Numerous fungi, largely pathogenic taxa, develop resistance to multiple fungicides utilized in agricultural systems (Brent and Hollomon, 1998;Ma and Michailides, 2005;Price et al, 2015). Alvarez-P erez et al (2016) observed that some Metschnikowia strains display a "trailing" phenotype (reduced, but persistent growth) at concentrations above the noted minimum inhibitory concentration observed for synthetic fungicides tested in their study. While this "trailing" phenotype may be a consequence of the assay procedure, it may also suggest inter-and intra-specific variation in susceptibility, which could allow for evolution of resistance.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Numerous fungi, largely pathogenic taxa, develop resistance to multiple fungicides utilized in agricultural systems (Brent and Hollomon, 1998;Ma and Michailides, 2005;Price et al, 2015). Alvarez-P erez et al (2016) observed that some Metschnikowia strains display a "trailing" phenotype (reduced, but persistent growth) at concentrations above the noted minimum inhibitory concentration observed for synthetic fungicides tested in their study. While this "trailing" phenotype may be a consequence of the assay procedure, it may also suggest inter-and intra-specific variation in susceptibility, which could allow for evolution of resistance.…”
Section: Resultsmentioning
confidence: 93%
“…Both metconazole (triazole) and penthiopyrad (carboxamide) are broad‐spectrum fungicides effective against many fungal pathogens that target fruit, vegetable, and nut crops. Recently, a suite of synthetic fungicides widely used in agriculture have also been shown to reduce the performance of nectar‐inhabiting yeasts under laboratory conditions (Álvarez‐Pérez et al ., ; Bartlewicz et al ., ), including numerous members of the Metschnikowia clade. Moreover, experimental application of these fungicides to the flowering plant Linaria vulgaris revealed that these effects can also occur in‐situ (Bartlewicz et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy of azoles for disease control often remains contradictory, presumably due to the difficulty of timing and targeting fungicides to heads [ 3 ] and the apparently increased resistance of fungi to this fungicide class [ 4 ]. In addition, azole residues can disperse and persist in the environment due to repeated use of these fungicides [ 5 , 6 , 7 ], which have a considerable impact on ecosystem health and functionality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Metschnikowia of the family Metschnikowiaceae (Order Saccharromycetales ) comprises single-celled species that reproduce via budding of vegetative cells and is characterized by the presence of one or two needle-shaped ascospores on elongated asci (Mendonca-Hagler et al 1993 ; Pretorius 2000 ; Marinoni et al 2006 ; Kuan et al 2016 ). A total of 35 Metschnikowia species have been described to date in a wide range of hosts, including flowers, fruits, flower-pollinating insects, and lacewings (Mendonca-Hagler et al 1993 ; Lachance et al 2005 ; Guzmán et al 2013 ; De Vega et al 2014 ; Kuan et al 2016 ; Álvarez-Pérez et al 2016 ). Yeasts provide a variety of unique bioactive metabolites that have medicinal importance (Mager and Winderickx 2005 ; VanderMolen et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%